Effectiveness of a Dietitian-led Healthy Lifestyle Education Package in Improving Health Behaviours of Stroke Survivors in Malaysia: A Pilot Study - Wong, Hui Jie; Harith, Sakinah; Lua, Pei Lin; Ibrahim, Khairul Azmi (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Despite a higher risk of a recurrent cerebrovascular event, many stroke survivors failed to achieve their targeted treatment goals. This study aimed to examine the effectiveness of a dietitian-led healthy lifestyle educational package targeted at improving stroke risk factors and lifestyle practices among stroke survivors. MATERIALS AND METHODS: A quasi-experimental pilot study was undertaken in general medical wards of two public hospitals in Malaysia. Patients were allocated into either intervention or control groups based on the week of screening. Adults aged more than 18 years old, with first-ever stroke, and the willingness of caregivers to participate were included. The intervention group (patient-caregiver dyad) received three dietitian-led healthy lifestyle education sessions underpinned with Health Belief Model and Reflection and Refractive theories and was followed up for three months. The control group received the usual stroke care. Outcome variables included blood pressure, body mass index, waist circumference, dietary intake, physical activity levels, smoking status, alcohol consumption, malnutrition risk, and health-related quality of life. McNemar, Chi-square, and repeated measures Analysis of Covariance tests were conducted to examine the within - and between-group differences. RESULTS: A total of 54 participants (27 in each group) were included in this study. The intervention group had a significantly lower intake of sugar (P=0.002, effect size=0.50) and sodium (P=0.044, effect size=0.31), a lower proportion of active smokers (7% versus 33%, P=0.039), lesser sitting time (P=0.012, effect size=0.37), and lower proportion having pain/discomfort issues (22% versus 63%, P=0.005) than the control group. CONCLUSION: Early dietitian-led lifestyle modification sessions underpinned with behavioural change theories paired with the involvement of family members appear to be beneficial among stroke survivors.